Pengaruh Keterampilan Kerja Dan Kompensasi Terhadap Produktivitas Kerja Karyawan Al-Markaz Collection - Nursefina Mulyani; Kusuma Agdhi Rahwana; Nita Fauziah Oktaviani (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This study aims to determine the effect simultaneously or partially of the Job Skills variable and the Compensation variable on Work Productivity. The population used in this study were 180 Al-Markaz Collection employees. The method used in this research is descriptive research with a quantitative approach. The sample selection uses a random sample. The sample used is using a random sampling sample with the slovin formula, namely 124 employees. Sources of data in this study are secondary data and primary data. The data analysis technique used was multiple linear regression with the help of SPSS 26. Based on the results of the study it was concluded that Work Skills and Compensation simultaneously have a significant effect on Work Productivity. Work Skills partially have a significant effect on Work Productivity. Compensation partially has a significant effect on work productivity.